Mucinose papulosa associada ao hipotireoidismo Papular mucinosis associated with hypothyroidism - Morgana Boeno Volpato; Tatiana Jerez Jaime; Martha Pisani Proença; Alexandre Carlos Gripp; Maria de Fátima Guimarães Scotelaro Alves (Sociedade Brasileira de Dermatologia, 2010)
A mucinose papulosa ou líquen mixedematoso é doença idiopática, manifestada por pápulas, nódulos ou placas por depósito de mucina na derme, na ausência de doença tireoidiana. Apresentamos um caso atípico, com lesões exuberantes em placas, associado ao hipotireoidismo subclínico. Nas mucinoses cutâneas há quantidade anormal de mucina na pele. Tradicionalmente as classificações consideram critério diagnóstico para mucinose papulosa a ausência de doença tireoidiana. Poucos casos associados ao hipotireoidismo são descritos e, assim como o nosso, constituem líquen mixedematoso atípico, sugerindo que a presença de doença tireoidiana não deva ser critério de exclusão para essa doença. Papular mucinosis or lichen myxedematosus is an idiopathic disorder characterized by papules, nodules or plaques caused by mucin deposition in the dermis, in the absence of thyroid disease. The present report describes an atypical case with exuberant lesions in the form of plaques, associated with subclinical hypothyroidism. In cutaneous mucinosis, there is an abnormal quantity of mucin in the dermis. In traditional classifications of papular mucinosis, an absence of thyroid disease constitutes a diagnostic criterion. A few cases of the disease have been reported in association with hypothyroidism constituting, as in the present case, atypical lichen myxedematosus. It is therefore suggested that the presence of thyroid disease should not be considered an exclusion criterion for the diagnosis of this condition.